Do Macroeconomic Crises Always Slow Human Capital Accumulation? - Schady, Norbert R. (Washington, DC: World Bank, 2014)
The impact of macroeconomic crises on the investments made by parents in the human capital of their children is a question of considerable policy importance. Analysis of the effects of the profound 1988-92 macroeconomic crisis in Peru on the schooling and employment decisions of school-age children in urban areas finds no effect on attendance rates but a significant decline in the fraction of children who are both employed and attend school. It also finds significantly higher mean educational attainment for children exposed to the crisis than for those who were not. These findings may be related: children who are not employed have more time available and may therefore put more effort into school.